Guide to Recruitment A Manual for Head Start Personnel in Recruiting Handicapped Children - Chapel Hill Training-Outreach Project, NC.; Hodskins, David; Chapel Hill Training-Outreach Project, NC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
Intended for Head Start personnel, the manual outlines a recruitment campaign for identifying and enrolling children who have health impairments requiring special education and related services. Briefly covered are the following topics: rationale for the recruitment compaign; targets of recruitment (which include Head Start families, the general public, health and social services, and agencies serving the disabled); an overview of advertising; history of advertising; the use of newspapers, radio, television, outdoor advertising, and promotional activities (along with the advantages and disadvantages of each); detailed guidelines for using recruitment strategies; and evaluation of recruitment efforts. Appended are sample copy for a radio spot, a sample news release, a sample direct mail letter, a slide-tape script, and recruitment evaluation forms. (SBH)
Sponsoring Agency: Office of Child Development (DHEW), Washington, DC.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advertising; Guidelines; Handicapped Children; Identification; Information Dissemination; Intervention; Preschool Education; Public Relations; Publicize; Referral; Project Head Start; Guides, General